Tibetan medicine Pa Zhu Wan ameliorates carbon tetrachloride-induced liver fibrosis in rats by regulating the TGF-β-Smad2/3 and IL-6/JAK2/STAT3 signaling pathways - Zhao, Linlin; Jiang, Yan; Ma, Jing; Yang, Yongjing; Liu, Guo; Wang, Zhengxing; Wong, Tin Wui; Zhang, Dejun (Frontiers in Pharmacology, 2025)
BackgroundPa Zhu Wan (PZW) is a Tibetan medicine with natural actives potentially for liver fibrosis treatment. This study determines the therapeutical effects and mechanisms of actions of PZW on carbon tetrachloride-induced hepatic fibrosis in rats.MethodsThe chemical profiles of PZW and its serum metabolites were assessed. The liver elasticity of rats with hepatic fibrosis (induced by carbon tetrachloride-olive oil mixture 1:3 v/v, 0.5 mL/kg) was evaluated against intragastric-fed PZW (0, 60, 120, 240 mg/kg body weight daily for 8 weeks) vs. ursodeoxycholic acid (positive control) with normal rats as negative control by shear wave elastography system (n = 8/group). The serum aminotransferase (ALT and AST), alkaline phosphatase (ALP), bilirubin (TBIL and DBIL), bile acid, inflammatory cytokines (IL-6, IL-1β, TNF-α) and liver fibrosis indicator (HA, LN, PC-III and IV-C) concentrations were measured by ELISA kits. Pathological changes and collagen deposition extent of liver were characterized by immunoassay and H&E/Sirius red/immunohistochemical staining. The expressions of MMP1, TIMP1, IL-6, JAK2, STAT3, p-JAK2, p-STAT3, TGF-β, Smad2/3 and p-Smad2/3 were determined by Western blotting technique.ResultsPiperine, trehalose, mulberroside F, chebulic acid, gallic acid and hydroxysafflor yellow A were main compounds of PZW. PZW alleviated liver fibrosis in a dose-dependent manner with reduced fibrous connective tissue/collagen, pseudolobules and inflammatory cell infiltration. The serum IL-1β, IL-6, TNF-α, TBIL, DBIL, ALT, AST and ALP levels decreased with rats treated with PZW where reduced liver inflammation halted its fibrosis and improved overall hepatic health. PZW mitigated hepatic fibrosis in association with IL-6/JAK2/STAT3 and TGF-β/Smad2/3 signaling pathway inhibition favoring MMP1/TIMP-1 ratio that attenuated collagen deposition and promoted collagen degradation.ConclusionPZW alleviated hepatic fibrosis in vivo, primarily by inhibiting collagen accumulation through navigating IL-6/JAK2/STAT3 and TGF-β/Smad2/3 signaling pathways.